Induction of labour outcomes in a tertiary hospital: the Ghanaian cervix and misoprostol 25ug (GCAM-25 STUDY)—a cross-sectional study - Teresa Aba Mensah; Kwaku Asah-Opoku; Kwame Adu-Bonsaffoh; Evans Kofi Agbeno (BMC Pregnancy and Childbirth)
Abstract Background Induction of labour is an indispensable obstetric procedure, although associated with some complications. The World Health Organization recommends the use of low dose misoprostol to reduce adverse induction outcomes like uterine hyperstimulation and rupture. With the current availability of 25ug misoprostol tablets in Ghana, this study assesses the effectiveness and safety of 25ug intravaginal misoprostol among women with low risk postdate pregnancies (between 41 weeks and 43 weeks) induced at the premier tertiary healthcare facility in the country. Methods A cross-sectional study of low risk postdate pregnant women scheduled for induction of labour at Korle- Bu Teaching Hospital between 21st July 2022 and 30th April 2023. The primary outcome was the mode of delivery following induction of labour. The secondary outcomes included: induction to delivery interval, maternal complications, fetal complications and the predictors of successful vaginal delivery. Results Among 168 women analysed, 138/168 participants (82.1%) had vaginal delivery and 30/168 participants (17.9%) had caesarean section. The commonest indication for caesarean section was failure to progress, accounting for 40% of cases. The proportion of postdate women that had vaginal delivery within 24 h of induction was 117/168 (69.6%) with a CI of 62.1–76.5. The mean induction to vaginal delivery time was 17.39 (± 7.31) hours. There were no cases of uterine rupture, hyperstimulation, maternal mortality or still births recorded during the study. Fetal heart rate abnormalities occurred in 8.9% of participants, meconium staining of liquor occurred in twenty-five participants (14.9%). Eleven babies (6.5%) had low APGAR score (< 7) at five minutes and seventeen babies (10.1%) required NICU admission. Parity was the only significant predictor of vaginal delivery. (OR 3.14, 95% CI:1.38–7.13) Conclusion The 25ug misoprostol induction protocol is effective and safe for the Ghanaian population with low risk postdate pregnancy.